Non-shivering thermogenesis is differentially regulated during the hibernation season in Arctic ground squirrels - Hunstiger, Moriah; Johannsen, Michelle Marie; Oliver, S. Ryan (Frontiers in Physiology, 2023)
Arctic ground squirrels are small mammals that experience physiological extremes during the hibernation season. Body temperature rises from 1°C to 40°C during interbout arousal and requires tight thermoregulation to maintain rheostasis. Tissues from wild-caught Arctic ground squirrels were sampled over 9 months to assess the expression of proteins key to thermogenic regulation. Animals were sacrificed while aroused, and the extensor digitorum longus, diaphragm, brown adipose tissue, and white adipose tissue were probed using Western blots to assess protein expression and blood was sampled for metabolite analysis. Significant seasonal expression patterns emerged showing differential regulation. Contrary to our prediction, white adipose tissue showed no expression of uncoupling protein 1, but utilization of uncoupling protein 1 peaked in brown adipose tissue during the winter months and began to taper after terminal arousal in the spring. The opposite was true for muscular non-shivering thermogenesis. Sarco/endoplasmic reticulum calcium ATPase 1a and 2a expressions were depressed during the late hibernation season and rebounded after terminal arousal in diaphragm tissues, but only SERCA2a was differentially expressed in the extensor digitorum longus. The uncoupler, sarcolipin, was only detected in diaphragm samples and had a decreased expression during hibernation. The differential timing of these non-shivering pathways indicated distinct functions in maintaining thermogenesis which may depend on burrow temperature, availability of endogenous resources, and other seasonal activity demands on these tissues. These results could be impacted by fiber type makeup of the muscles collected, the body weight of the animal, and the date of entrance or exit from hibernation.